E-Book with Problem Based Learning to Improve Student Critical Thinking in Science Learning at Elementary School - Susanto, Teguh Trianung Djoko; Dwiyanti, Putri Bestari; Marini, Arita; Sagita, Julius; Safitri, Desy; Soraya, Evitha (International Journal of Interactive Mobile Technologies (iJIM), 2022)
With the development of technology, especially in the world of education, teachers must have learning media that attracts students' attention, one of which is E-Books. This study aims to determine whether Problem Based Learning-Based E-Books Can Improve Students' Critical Thinking Ability in Primary School Science Learning. This research was conducted on elementary school students in the district of Jagakarsa, South Jakarta. This research method uses the RnD method. In this research. To get the results, the researchers used a pre-test and also a post-test to get the results. The results show that this E-Book is able to improve critical thinking skills in science learning as digital media innovation, narration, video and also practice questions.